Natural convection of hybrid nanofluid flow in the presence of multiple vertical partial magnetic fields in a trapezoidal shaped cavity - Geridonmez, Bengisen Pekmen; Öztop, Hakan Fehmi (Springer Heidelberg, 2022)
In this paper, a numerical investigation on natural convection flow of silver(Ag)-magnesium oxide(MgO)-water hybrid nanofluid in a trapezoidal shaped cavity under the effect of partial magnetic fields is carried out. Unsteady, dimensionless governing equations in stream function-vorticity formulation are approximated by radial basis functions (Rbfs) in space and the fourth order backward differentiation formula in time. Pseudo time derivative in stream function equation is also taken into account. Brinkman model for dynamic viscosity and Xue's model for thermal conductivity are adopted. The pertinent observed parameters are Rayleigh number (10(4) <= Ra <= 10(6)), Hartmann numbers (0 <= Ha(1), Ha(2) <= 100), equally weighted concentration of nanoparticles (0 <= phi(1) , phi(2) <= 0.01), tilt angle of oblique walls (0 <= theta <= pi/9) and the lengths of the partial magnetic fields (0.5 <= l(b1), l(b2) <= 1). The large area of impact region of partial magnetic field results in inhibition of fluid flow and heat transfer.
Keywords: Mhd Mixed Convection; Heat-Transfer; Entropy Generation; Numerical-Simulation; Porous-Medium; Enclosure; Irreversibility; Conductivity; Impact